(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article is devoted to the management of monopolies in the industry and the development of competition. Experiences of the world scale were analyzed, it was determined that they would be a model for Uzbekistan, and promising proposals were made for the effective management of monopoly and improvement of competition.